Q6) ii

Q6) ii 11:53 o. 00K/s t 4G VoLTE Sayalee Ambulkar 1 day Iii,i oaaa

Dear Student,

Given : y=tan-1(5x+13-x-6x2)To Find :dydx solution : y=tan-1(5x-13-x-6x2)applying ddx both the sidesddx(y)=ddx{tan-1(5x-13-x-6x2)}dydx=d{tan-1(5x-13-x-6x2)}d(5x-13-x-6x2)×d(5x-13-x-6x2)dx      [using Chain Rule]dydx=11+(5x-13-x-6x2)2×(3-x-6x2)(5-0)-(5x-1)(-1-12x)(3-x-6x2)2 dydx=1(3-x-6x2)2+(5x-1)(3-x-6x2)2×5(3-x-6x2)2+5x+60x2-1-12x(3-x-6x2)2dydx=(3-x-6x2)2(3-x-6x2)2+(5x-1)×5(9+x2+36x4-6x+12x3-36x2)+60x2-7x-1(3-x-6x2)2dydx=45-175x2+180x4-30x+60x3+60x2-7x-1(9+x2+36x4-6x+12x3-36x2)+(5x-1)dydx=180x4+60x3-115x2-37x+4436x4+12x3-35x2-x+8
Hope this information will clear your doubts about topic.       

If you have any more doubts just ask here on the forum and our experts will try to help you out as soon as possible.       

Keep posting!!       


  • 0
Please find this answer

  • 0
What are you looking for?